Analysis of Physics Concepts on Local Wisdom of Picking the Sea of Situbondo as a Source for Learning Physics in SMA - Aida Nurul Safitri; Vidya Matarani Salma (Experimental Student Experiences, 2023)
Local wisdom is a view of life, knowledge, understanding and belief as well as habits carried out by local people in the form of activities. The local wisdom of the Situbondo people is defined as activities owned by the Situbondo people which have been proven to be preserved to date. One example is the sea picking tradition. The sea picking tradition is a traditional ceremony or ritual performed by throwing offerings into the middle of the sea. In sea-picking tradition there are many physics concepts in it so that the integration of sea picking local wisdom into physics learning in high school is very necessary. This study was designed to analyze that in the sea picking tradition there are physics concepts that can be used as learning resources in high school. This research is a qualitative research. Data collection techniques using interviews, observation and literature study. Data were analyzed descriptively. Results this study were obtained from the sea picking tradition by identifying physics concepts, especially in Newton's II and III Laws, pressure, Archimedes' law and waves. Thus, the analysis of physics concepts in the sea picking tradition can be used as an alternative source of learning physics in high school.